2021
DOI: 10.2147/ijgm.s320713
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of Deceased COVID-19 Patients

Abstract: Objective: Fatalities due to coronavirus disease 2019 continue to increase, and information on the epidemiological and clinical characteristics of deceased patients who were hospitalized with COVID-19 is limited in the Arab region. The current study aimed to address this gap. Methods: Three hundred and four Saudi patients in Jazan Region, Saudi Arabia, who died after being hospitalized with COVID-19 between July 1, 2020, and December 31, 2020, were analyzed in this retrospective cohort study. Results: A great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(57 reference statements)
3
11
0
1
Order By: Relevance
“…[7][8][9] In the present study, most hospitalized COVID-19 patients with ESKD were aged ≥ 65 years and had two or more pre-existing comorbidities, such as hypertension, diabetes, and cardiovascular disease, which are common in patients with ESKD and are associated with increased disease severity and mortality risk. 4,5,15 We found that the mortality risk in COVID-19 patients with ESKD and cardiovascular disease was fourfold higher than that in the others. These results are consistent with those of a previous study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[7][8][9] In the present study, most hospitalized COVID-19 patients with ESKD were aged ≥ 65 years and had two or more pre-existing comorbidities, such as hypertension, diabetes, and cardiovascular disease, which are common in patients with ESKD and are associated with increased disease severity and mortality risk. 4,5,15 We found that the mortality risk in COVID-19 patients with ESKD and cardiovascular disease was fourfold higher than that in the others. These results are consistent with those of a previous study.…”
Section: Discussionmentioning
confidence: 71%
“…In terms of disease severity, the most common factors associated with poor prognosis include advanced age and the presence of pre-existing comorbidities, such as chronic kidney disease. 4 , 5 While acute respiratory failure due to diffuse alveolar damage is the main clinical characteristic of COVID-19, the kidneys are one of the most common extrapulmonary targets of the virus. 6 In line with this information, a previous study revealed that the mortality risk in patients with kidney disease was more than threefold higher than that in others.…”
Section: Introductionmentioning
confidence: 99%
“…These findings correlate with the increase in disease severity reported in a previous study. [ 30 ] In other research, an elevation in serum lactate dehydrogenase levels was used as a marker of disease severity and the development of pulmonary fibrosis after acute lung injury, suggestive of the destruction of pulmonary tissue, and a correlation with increased mortality risk. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea was the most common presenting complaint in the present study which is consistent with the finding of other studies. 10 , 11 Approximately 73.6% of the patients complained of dyspnea at the time of presentation, and 78.3% of the patients were in a dire need of an ICU admission.…”
Section: Discussionmentioning
confidence: 99%